Effect of Financial Technology and Environmental Performance on Financial Performance with Corporate Social Responsibility as Intervening Variables - Ni Wayan Novi Budiasni; Kadek Indrayani; Zainol Mustafa (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine the effect of financial technology and environmental performance on financial performance, with corporate social responsibility as an intervening variable. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2018-2022. The technique used to take samples in this study is purposive sampling. The number of samples in this study was 10 companies. This study’s data type is secondary timer series data with 5 years of observation. The research data was analyzed using SEM-PLS with the assistance of the SmartPLS version 3 application. Financial technology and environmental performance do not affect financial performance, financial technology does not affect CSR, environmental performance has a positive and significant effect on CSR, CSR has a positive and significant effect on financial performance, CSR does not mediate the effect of financial technology on financial performance, and CSR mediates the effect of environmental performance on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022.